2009
DOI: 10.1159/000209378
|View full text |Cite
|
Sign up to set email alerts
|

Urodilatin and Pentoxifylline Prevent the Early Onset of <i>Escherichia coli</i>-Induced Acute Renal Failure in a Model of Isolated Perfused Rat Kidney

Abstract: Background/Aims: Raised cytokine levels and a hypoperfusion-associated decrease in glomerular filtration rate (GFR) are hallmarks of the genesis of septic acute renal failure (ARF). Therefore, anti-inflammatory as well as renal vasodilating therapeutic strategies may afford renal protection during septic ARF. The present study was designed to determine the effects of administration of urodilatin, pentoxifylline and theophylline to improve renal function in an ex-vivo model of ‘septic renal injury’. Methods: Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…It can be postulated that the significant decrease of HCO 3 − in LPS‐treated rats compared to PD‐4‐I may be a sign of acute kidney injury (AKI) with acute loss of tubule cell function and impaired reabsorption of filtered HCO 3 − . In this respect experimental and clinical studies suggested potential protective renal effects of PDI by endothelium‐dependent vascular relaxation (Groesdonk et al 2009). Although this was not specifically addressed in our study we suggest that PD‐4‐I application may prevent prerenal AKI by improvement of fluid balance in septic shock in our model.…”
Section: Discussionmentioning
confidence: 99%
“…It can be postulated that the significant decrease of HCO 3 − in LPS‐treated rats compared to PD‐4‐I may be a sign of acute kidney injury (AKI) with acute loss of tubule cell function and impaired reabsorption of filtered HCO 3 − . In this respect experimental and clinical studies suggested potential protective renal effects of PDI by endothelium‐dependent vascular relaxation (Groesdonk et al 2009). Although this was not specifically addressed in our study we suggest that PD‐4‐I application may prevent prerenal AKI by improvement of fluid balance in septic shock in our model.…”
Section: Discussionmentioning
confidence: 99%
“…It can also affect the microcirculatory blood flow and contribute to the attenuation of interstitial inflammation, down regulation of monocyte chemo-attractant protein-1 gene expression, reduction in the expression of mitogenic and profibrogenic genes, and suppression of the proliferation of interstitial fibroblast and glomerulomesangial cells [8]. However, the preclinical data with regard to PTX and AKI seems controversial [9,10]. The effect of PTX in reducing renal injury by measuring sCr and α-1-microglobulin was investigated and ameasuring sCr and beneficial role of PTX on the prevention of kidney injury was observed [11].…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro isolated perfused rat kidney model has been extensively utilized for investigating renal drug handling and the effects of drugs and various substances on renal vasculature , glomerular function , renal cellular metabolism , and gluconeogenesis . However, the model has not been tested for the investigation into etiologic factors causing changes in renal histology.…”
Section: Discussionmentioning
confidence: 99%